Effect of Ischemic Preconditioning on Marathon-Induced Changes in Serum Exerkine Levels and Inflammation - Mieszkowski, Jan; Stankiewicz, Błażej; Kochanowicz, Andrzej; Niespodziński, Bartłomiej; Borkowska, Andżelika; Antosiewicz, Jędrzej (Frontiers in Physiology, 2020)
Participation in a long-distance run, e.g., marathon or ultramarathon, continues to increase. One side effect of long-distance running is excessive inflammation manifested by the rise in inflammatory cytokine levels. We here aimed to elucidate the effects of 10-d ischemic preconditioning (IPC) training on marathon-induced inflammation and to evaluate the role of serum-stored iron in this process. The study involved 19 recreational runners taking part in a marathon. IPC training was performed in the course of four cycles, by inflating and deflating a blood pressure cuff at 5-min intervals (IPC group, n = 10); the control group underwent sham training (n = 9). The levels of inflammatory and others markers (FSTL-1, IL-6, IL-15, leptin, resistin, TIMP-1, OSM, and LIF) were measured before and 24 h after training; and before, immediately after, and 24 h and 7 d after the marathon. The 10-d IPC training increased serum leptin levels. IL-6, IL-10, FLST-1, and resistin levels were increased, while TIMP-1 levels were decreased in all runners after the marathon. The changes were significantly blunted in runners from the IPC group compared with the control group. Baseline serum iron levels correlated with IL-6 and FSTL-1 levels; serum ferritin correlated with IL-6, FSTL-1, and resistin levels after the marathon. Conversely, serum TIMP-1 levels inversely correlated with serum iron levels. Although not evident at baseline, IPC training significantly reduced marathon-induced inflammation. In addition, the reduced responsiveness and attenuation of running-induced inflammation were inversely related to baseline serum iron and ferritin levels.